Human dignity as a foundation of law: proceedings of the Special Workshop held at the 24th World Congress of the International Association for Philosophy of Law and Social Philosophy in Beijing, 2009 - Brugger, Winfried; Kirste, Stephan (Archiv für Rechts- und Sozialphilosophie – Beihefte, 2013)
Although human dignity is an old principle in philosophy, the history of its legal form is relatively short. Since its first adoption in the preamble of the Irish Constitution and the Universal Declaration of Human Rights it has more and more proven to be a fundamental principle of law. The philosophers, lawyers and political scientists joint in this e-book discuss this assumption with respect to the legal form of dignity, its relation to values like freedom and autonomy, and analyze its implications for justice in difficult decisions. Because of the fundamental value of human dignity, comparative studies are intended to show its relevance in different legal orders and in international law.